Editorial - Vieira, Wilson; Cepêda, Vera Alves; Malta, Maria Mello de (Cadernos do Desenvolvimento, 2022)
Editorial. Cadernos do Desenvolvimento, Rio de Janeiro, Centro Celso Furtado, v. 17, n. 31, jan.-abr. 2022.